Acceptability of the effective strain damage model for fatigue life assessment considering the load sequence effect for automotive coil spring. (August 2021) - Chin, C.H.; Rahim, A.A.A.; Abdullah, S.; Singh, S.S.K.; Md Nor, N.
Highlights: Loading histories signals of coil spring were acquired via road tests. Load sequence effects in strain loading histories was examined. Effective strain damage model was applied for durability predictions. Load sequence effects were more significant in signals with high amplitude events. Abstract: This paper aims to assess the effective strain damage (ESD) model with a durability analysis of an automobile coil spring under consideration of the load sequence effect. Conventional strain-life models such as Coffin-Manson, Morrow and Smith-Watson-Topper are insufficient in predicting fatigue life under the consideration of the load sequence effect. Strain time histories of coil springs were captured based on three types of road conditions: highway, campus and industrial roads. In order to determine the fatigue life, the ESD and conventional strain-life models were employed. The strain-life models predicted lower fatigue life values for campus and industrial roads, which contained many high amplitude events. Similar fatigue life predictions for ESD and conventional strain-life models were found on the highway due to the absence of high amplitude events, which led to a minimal load sequence effect. The suitability of the ESD model was verified through the Weibull probability plot, in which the ESD model fitted well to the distribution compared to conventional strain-life models. The main contribution is that load interactions have a significant influence on predicting fatigue life within the random strain histories of the fatigue properties of a coil spring.